RESILIENCE AND RECOVERY OF HEALTHCARE SYSTEMS POST-EMERGENCY: NIGERIAN CONTEXT - UGWU, Eunice Ngozi (Multi-Disciplinary Research and Development Journals Int'l, 2025)
Healthcare systems play a critical role in protecting population health during and after public health emergencies. In Nigeria, recurrent crises such as COVID-19, Ebola, cholera, Lassa fever, and climate-related disasters have exposed persistent weaknesses in preparedness, service continuity, and post-emergency recovery. This study examines the resilience and recovery of Nigeria’s healthcare system following public health emergencies, with emphasis on leadership, workforce capacity, resource availability, and system adaptation. A mixed-methods cross-sectional design was employed across tertiary, secondary, and primary healthcare facilities in three geopolitical zones. Quantitative data were collected from 600 healthcare personnel using standardized resilience assessment tools, while qualitative insights were obtained through focus group discussions and in-depth interviews with health workers and administrators. Findings indicate that tertiary facilities demonstrated higher resilience and faster recovery compared to primary healthcare centers, which remained constrained by limited infrastructure, funding, and coordination. Leadership engagement, staff training, and prior emergency experience were significantly associated with improved service continuity and recovery outcomes. Qualitative findings highlighted adaptive leadership and workforce commitment as key enablers, alongside systemic challenges such as underfunding and supply chain disruptions. The study concludes that health system resilience in Nigeria is uneven and underscores the need for targeted investments in leadership development, workforce capacity building, and strengthening of primary healthcare systems to ensure equitable recovery and preparedness for future emergencies.